International Trade in Services Scale - Liberalization - Profits - Rymarczyk, Jerzy (Międzynarodowy handel usługami : rozmiary - liberalizacja - korzyści, 2010)
The paper presents the scale of international trade in services as well as it outlines the course of service negotiations run within WTO and enumerates potential advantages which may be attained by states in case of the total liberalization of this sector. The analysis shows that the liquidation of protection barriers imposed on trade in services may generate a lot of advantages for the states. It should induce WTO members to finish negotiations held in the frameworks of Doha Development Agenda (DDA) quickly.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 173-183
Keywords: services; international trade; liberalization; WTO; GATS; Doha Development Agenda